Why We Don't Rent What Others Love: The Role of Product Attachment in Consumer‐to‐Consumer Transactions - Graul, Antje R. H.; Brough, Aaron R. (Journal of Consumer Psychology, 2021)
When listing a possession for rent on a consumer‐to‐consumer platform, owners typically write a brief product description. Such descriptions often include attachment cues—indications that the owner is emotionally attached to the product. How does knowing that an owner is sharing a possession that has sentimental value impact rental likelihood? Evidence from secondary data and four experiments suggests that although some owners mistakenly expect attachment cues to enhance a product's appeal, attachment cues instead tend to deter prospective renters. We attribute this effect to renters' desire to avoid the responsibility of protecting (e.g., from damage, loss, or theft) an item to which the owner is emotionally attached. Whereas prior research has examined how product attachment influences owners' decisions, we show how an owners' expression of attachment affects others involved in a transaction. By refuting the lay theories of some owners about how to attract renters, our findings provide practical implications for owners and the platforms that connect them to users in the multi‐billion‐dollar consumer‐to‐consumer rental market.